An efficient, room temperature, oxygen radical anion (O2•-) mediated, one-pot, and multicomponent synthesis of spirooxindoles - Gajaganti S.; Bajpai S.; Srivastava V.; Singh S. (My University, 2025)
The present report highlights an efficient use of oxygen radical anion to promote a room temperature multi-component synthesis of spirooxindoles (4a-4l) under mild reaction conditions. The potassium superoxide (KO2) and tetraethylammonium bromide (TEAB) combination generate the oxygen radical anion in situ to promote this transformation. This method offers a sustainable and direct access to the biologically important spirooxindole derivatives in good to excellent yields. © 2017 Published by NRC Research Press.